Research on power grid capital project planning based on energy storage integration - TANG Xian; LIN Yinyin; CHEN Yongshu; ZHAO Chen; LI Qianying (Diance yu yibiao)
Grid companies can earn significant revenue from energy storage system for energy time conversion and can alleviate line congestion during peak periods, so project investment decisions in the power grid must take into account the potential impact of commercial energy storage on grid operations. In this paper, a three-level model is proposed to jointly optimize the site size of commercial energy storage and grid capacity expansion. In the optimization model, the upper-level model aims to maximize the lifetime profit of energy storage investment while ensuring a certain return on investment; the middle-level model optimizes the centralized decision of grid project investment; and the lower-level model simulates the market clearing. The proposed optimization problem is reduced to a two-level equivalent problem and solved using column & constraint generation methods. The proposed approach is tested on a 280-bus system with 556 feeders, and the results show that the proposed approach achieves more operational cost savings considering all three investment scenarios, demonstrating the effectiveness of the proposed approach.